PENGARUH PENGETAHUAN KEWIRAUSAHAAN DAN LINGKUNGAN KELUARGA TERHADAP KESIAPAN BERWIRAUSAHA MELALUI EFIKASI DIRI - Rahmad Fajar Royyan; Triesninda Pahlevi (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2022)
This article discusses a study about the effect of entrepreneurship on entrepreneurial readiness, family environment on entrepreneurial readiness,self-efficacy on entrepreneurial readiness, entrepreneurial knowledge on entrepreneurial readiness mediated by self-efficacy, and family environment on entrepreneurial readiness mediated by self-efficacy. The population of the study involved 141 students in class XII of the Office Administration Automation skill program at SMK Negeri Mojoagung who had taken the Creative Products and Entrepreneurship learning subject. A simple random sampling technique was used to select the sample and 104 respondents. The technique of the study used quantitative research with the type of a causal associative, and the data collection method used a questionnaire. The technique of data analysis used path analysis. The conclusion indicated that entrepreneurial knowledge has a positive and significant effect on entrepreneurial readiness (P Value = 0.008), the family environments did not have a positive effect on entrepreneurial readiness (P Value = 0.182), self-efficacy has a positive and significant effect on entrepreneurial readiness (P Value = 0.019), there is no significant effect on entrepreneurial readiness mediated by self-efficacy (P Value = 0.068), and family environment on entrepreneurial readiness mediated by self-efficacy has a positive and significant effect with the significant impact (P Value = 0.049).